2015
DOI: 10.1039/c4ay03103b
|View full text |Cite
|
Sign up to set email alerts
|

Rapid classification and identification of complex chemical compositions in traditional Chinese medicine based on UPLC-Q-TOF/MS coupled with data processing techniques using the KuDieZi injection as an example

Abstract: KuDieZi (KDZ) injection is prepared by extracting and processing Ixeris sonchifolia [Ixeris sonchifolia Hance] belonging to Lactuca genus of the Asteraceae family. KDZ injection is a single-herb preparation in which components are analysed by liquid chromatographymass spectrometry. However, the chemical compositions of this preparation are complex and diverse. Hence, data processing is complicated and time consuming; furthermore, data processing can not provide a systematic, accurate and repeatable method to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…Similarly, other metabolites including M18, M20, M22, M24, M25, M27–M31, M33–M37, M39–M41, M43–M47 were also tentatively identified, and the detailed results are summarized in Table . It also indicated that methylation, dehydrogenation, demethylation, methylation, deglycosylation, glucuronidation, and sulfation were the main metabolic pathways of flavonoids in Kudiezi injection in rats, which was also in agreement with previous research .…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Similarly, other metabolites including M18, M20, M22, M24, M25, M27–M31, M33–M37, M39–M41, M43–M47 were also tentatively identified, and the detailed results are summarized in Table . It also indicated that methylation, dehydrogenation, demethylation, methylation, deglycosylation, glucuronidation, and sulfation were the main metabolic pathways of flavonoids in Kudiezi injection in rats, which was also in agreement with previous research .…”
Section: Resultssupporting
confidence: 91%
“…In the same fashion, by comparing the retention behaviors, MS/MS fragmentation, characteristic fragmentation patterns of prototypes as well as knowledge of metabolism, other metabolites were also tentatively identified and the detailed results are summarized in Table . The results revealed that reduction, methylation, hydration, oxidation, glucuronidation, and sulfation were the main metabolic pathways of organic acids in Kudiezi injection in rats, which was in agreement with several previous researches .…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations